Bir Hospital of Yore and Now - Dixit, Hemang (Journal of Kathmandu Medical College, 2015)
The setting up of the Bir Hospital about 125 years ago and its development over the years as a service and teaching institute is described. Journal of Kathmandu Medical CollegeVol. 3, No. 4, Oct.-Dec., 2014Page: 177-180